Systemic review: Pharmacognosy, phytochemistry, pharmacology and clinical applications of Gymnema sylvestre R Br. - Gurav, Shailendra; Gulkari, Vijay; Duragkar, Nandkishore; Patil, Arun (Pharmacognosy Reviews)
Gymnema sylvestre R Br. (Gurmar) is a tropical vine whose leaves are considered antidiabetic in Ayurvedic medicine. It has been commonly used for the diabetes and as a diuretic in Indian proprietary medicines. This review attempts to encompass the available literature on Gymnema sylvestre with respect to its pharmacognostic characters, traditional uses, chemical constituents and summary of its various pharmacological activities and clinical effects. Other aspects such as toxicology and precautions are also discussed.
Keywords: Gymnema sylvestre R Br.; pharmacology; clinical application; chemistry